New insight into the metabolic mechanism of a novel lipid-utilizing and denitrifying bacterium capable of simultaneous removal of nitrogen and grease through transcriptome analysis - Tong, Yaobin; Li, Yiyi; Qin, Wenpan; Wu, Shengchun; Xu, Weiping; Jin, Peng; Zheng, Zhanwang (Frontiers in Microbiology, 2023)
A heterotrophic bacterium CYCN-C with lipid-utilizing and efficient nitrogen-removal abilities was identified as Pseudomonas glycinae. It could directly use fat, oil, and grease from kitchen waste (KFOG) as a carbon source with total nitrogen removal efficiency of 73.5%, which is significantly higher than that (60.9%) for sodium acetate. The expression changes of genes under exposure to KFOG and sodium acetate were analyzed by transcriptome sequencing. Results showed that genes cyo, CsrA, PHAs, and FumC involved in carbon metabolism under KFOG were significantly upregulated by 7.9, 17.0, 27.0, and 20.0-folds, respectively. The genes lipA, lipB, glpD, and glpK of the lipid metabolic pathway were upregulated by 1.6, 1.4, 22.5, and 2.3-folds, respectively. KFOG also improved the denitrification efficiency by inducing the expression of genes nar, nirB, nirD, and norR involved in the denitrification pathways. This work is the first to provide valuable insights into the genes expression of lipid-utilizing and denitrifying bacterium, and off a new approach for sewage treatment with reuse of KFOG wastes.